Assessing Water Quality in Nigerian Villages: An IoT-Based Monitoring of Three Rivers - Osifeko, Martins; Oduwole, Olamide; Kafar, Rasheedat (IPTEK The Journal for Technology and Science, 2024)
Ensuring safe and clean water is crucial for public health, especially in regions with limited access to reliable water quality testing. This study focuses on assessing water quality in three Nigerian villages using an IoT-based system. Traditional water quality monitoring methods are often expensive, time-consuming, and require specialized personnel and laboratory facilities. To overcome these challenges, we propose a low-cost, real-time water quality monitoring system utilizing the ESP32 microcontroller equipped with sensors for temperature, pH, dissolved oxygen, and conductivity. Our system collects and transmits data for continuous monitoring and analysis. The deployment in Nigerian villages along three rivers reveals that while pH levels are within safe limits, turbidity levels in two rivers exceed acceptable drinkingwater standards, highlighting the presence of particulate contamination. The system’s real-time capabilities and cost-effectiveness demonstrate its potential for broader application in resource-constrained areas. This study underscores the importance of IoT technologies in enhancing water quality monitoring and contributes to achieving the Sustainable Development Goals related to clean water and sanitation